Pengaruh Program Fullday School terhadap Pendidikan Karakter siswa di MAN 2 Padangsidimpuan - Khairani, Togu; Zulhimma , Zulhimma (Cognoscere: Jurnal Komunikasi dan Media Pendidikan, 2024)
: This study aims to investigate the influence of the Fullday School Program on students' character education at MAN 2 Padangsidimpuan. The research method used is qualitative with a case study approach. The research subjects consist of students at MAN 2 Padangsidimpuan who participate in the Fullday School Program. Research instruments used include interviews, observations, and document analysis. Data collection procedures were carried out by directly observing the behavior and character of students during the program period. Data were analyzed using thematic analysis techniques to identify patterns and main findings regarding the influence of the Fullday School Program on students' character education. The main findings indicate a significant improvement in characteristics such as discipline, responsibility, cooperation, and integrity among students after participating in the Fullday School Program. The implications of these findings underscore the importance of considering the Fullday School Program as an effective strategy in developing character education in secondary schools.